2018
DOI: 10.1002/app5.250
|View full text |Cite
|
Sign up to set email alerts
|

Tourism in Pacific island countries: A status quo round‐up

Abstract: In the 21st century, Pacific island countries (PICs) continue to leverage for tourism the attributes that have imbued them, including appeals to their cultural, geographical, and climatic allure. However, the questive than Southeast Asian destinations. ---This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…The common custodianship of natural and cultural resources underpins the motivation to be economically, socially, environmentally, and culturally sustainable, with partnerships integral to the process. Our findings are consistent with previous research that shows that businesses, if they are to be truly sustainable, must find their place within that setting and seek out ways to make partnerships mutually beneficial for all stakeholders (Cheer et al, 2018;Yap & Watene, 2019). The SDGs incorporate the role of culture in limited ways; the place of Indigenous values related to reciprocity and obligation within business operations (Bradly, 2015) and Indigenous landholding rights (Stumpf & Cheshire, 2019) are not accounted for.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The common custodianship of natural and cultural resources underpins the motivation to be economically, socially, environmentally, and culturally sustainable, with partnerships integral to the process. Our findings are consistent with previous research that shows that businesses, if they are to be truly sustainable, must find their place within that setting and seek out ways to make partnerships mutually beneficial for all stakeholders (Cheer et al, 2018;Yap & Watene, 2019). The SDGs incorporate the role of culture in limited ways; the place of Indigenous values related to reciprocity and obligation within business operations (Bradly, 2015) and Indigenous landholding rights (Stumpf & Cheshire, 2019) are not accounted for.…”
Section: Discussionsupporting
confidence: 88%
“…Pacific tourism has long established itself as an industry with the potential to enhance community development outcomes, often realized through local-level partnerships and respect for local cultural values and practices (Cheer et al, 2018;Movono, 2017). Research has shown that community relations, networks, and local level partnerships constitute a form of social capital for small businesses that can both strengthen and undermine the sustainability of SMEs (Movono & Becken, 2018).…”
Section: Small and Micro Tourism Enterprises Partnerships And Sustamentioning
confidence: 99%
“…In PICs, tourism is especially pivotal for poverty alleviation and offers opportunities for achieving broader development goals, such as those regarding infrastructure and employment [27]. The Pacific region showed a 4.9% increase of tourist arrivals between 2007 and 2017, with the largest portion attributed to all-inclusive, enclavic resorts, and cruise ship passengers [28] (p. 444). Harrison and Pratt [29] identified a split of Pacific tourism destinations into islands mainly attracting leisure tourists (e.g., Fiji, Tahiti, Vanuatu, etc.)…”
Section: Global Tourism Sector Developmentmentioning
confidence: 99%
“…However, the outrage is not based purely on the translation mistake, but also on the longstanding issue of non-Fijian staff with lack of local cultural understanding working for Tourism Fiji. The lack of care regarding local culture in tourism marketing is an ongoing issue in Fiji (Cheer et al, 2018;McMah, 2018). While demonstrating the omniscience of those working at Tourism Fiji (the lack of scrutiny of their activities), this case also highlights that not only tourists may lack understanding of local culture and social norms, but also businesses and DMOs.…”
Section: Stupidity In Destination Marketing Organizationsmentioning
confidence: 99%